Tobacco Smoking as A Risk Factor in DNA Methylation of Repair Gene (MLH1) Using Cytobbrush from Lateral Border of the Tongue - Muayad Hashim Matloob; Ameena Ryhan Diajil (Indian Journal of Forensic Medicine & Toxicology, 2022)
Objective: The aim of this study was to evaluate the epigenetic effect in the process of oral carcinogenesis by screening the methylation of repair gene in chronic tobacco smokers. Material and Method: Study design: One hundred male volunteers, divided into two groups: the 1stgroup consisted of 58 smokers, each consumed 20 cigarettes/day for at least 10 years; and the 2nd group consisted of 48non-smokers who were consider as a control group.The samples were taking from lateral border of the tongue by exfoliative cytology, and the extracted DNA was treated with phenol-chloroform gDNA,Screening of methylation was done by Methyl Specific PCR (MSP).Results :- The results of this studyshowed significant effect of tobacco smoking in methylation of MLH1 gene in site 1in comparison to non-smoker group,(P > 0.05), with Odds ratio = 4.957 CI ().